The Impact of Digitalization in Inheritance Law - Akmaljon A. Akramov; Nilufar Kh. Rakhmonkulova; Odilbek T. Khazratkulov; Elnora E. Inamdjanova; Diyora I. Imamalieva; Shakhzoda R. Tuychieva; Sayidkomil B. Ibodullaev; Azamat E. Ergashev; Shokhrukh Khamidov; Nodira R. Rustamova (Qubahan Academic Journal)
This article examines the emerging challenges and opportunities in regulating digital inheritance and trust management of digital assets. As individuals accumulate valuable digital assets, including cryptocurrencies, social media accounts, and online intellectual property, traditional inheritance frameworks are struggling to adapt. This study employs a comparative, interdisciplinary approach, integrating classical inheritance doctrines, modern digital asset theories, and principles of trust law. Key findings reveal significant gaps in current legal frameworks, particularly regarding asset identification, access rights, and jurisdictional authority. The study proposes a comprehensive digital trust framework encompassing ownership rights, trustee roles, jurisdictional considerations, data privacy, and liability limitations. Recommendations include new regulations for digital executors, formalized digital asset estate planning, and mechanisms to protect ownership interest’s post-mortem. This research contributes to the emerging field of digital inheritance law by offering both theoretical grounding and practical guidance for policymakers and legal practitioners navigating this rapidly evolving landscape.